Histopathological Study of Prostatic Lesions (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Prostatic disease is responsible for significant morbidity and mortality in men throughout the  world. Prostate cancer and benign prostatic hyperplasia are the two major prostate diseases that increase with  aging. Histopathological examination of prostatic lesions has been gold standard for the final diagnosis.  Objective: This study was carried out for histopathological evaluation of prostatic lesion and its correlation with  the clinical data. Materials and Methods: This study included all types of prostatic specimens received in  department of Pathology, AMC MET Medical College, Ahmedabad from January 2018 to December 2018.  Relevant clinical data was recorded. Results: The most common age group presenting with prostatic lesion was  60-69 years and the most common presenting clinical symptom was difficulty in micturation. The frequency of  benign and malignant lesions was observed to be 91% and 9% respectively. Amongst the benign lesions all  lesions were Benign Prostatic Hyperplasia (BPH) with or without associated pathological lesions. All the  malignant lesions were adenocarcinoma of prostate and were graded according to Gleasons scoring system.  Predominant malignant lesions (40%) revealed Gleasons score 9. Strong correlation of S.PSA level with prostatic  adenocarcinoma was seen in our study Conclusion: Histopathological evaluation seems to be gold standard for  diagnosis, prognosis and management of prostatic lesions. S.PSA level has strong correlation with the risk and  outcome of prostatic cancer.
Keywords: Prostate; Benign Prostatic Hyperplasia (BPH); Adenocarcinoma; Histopathology; S.PSA (Prostate Specific Antigen)